Does Quality of Social Media Marketing Affect Purchasing Decisions On Soba Padu SMEs? - Wibowo, Larasati Sukmadewi; Indriani, Ria; Haris, Miftahul Jannah Abdul (Jambura Agribusiness Journal, 2023)
Decreasing in sales of Soba Padu products nowadays, has an impact on SMEs that produce this traditional snack. Beside this condition, it is important to see what happen with the social media marketing as one of sales method on Soba Padu SMEs. This study aims to described the use of social media marketing in Soba Padu SMEs and to analyze effect of social media marketing on purchase decisions. Data sourced from primary data using 30 respondents that purchased Soba Padu. The data were analyzed using multiple regression analysis techniques. The results show that Soba Padu SMEs uses messenger features on Facebook and marketplaces as a communication tool in social media to the customers, and the producer uploaded photos and videos as promotion tools. The research finding are convenience (X1) and trust (X2) variable did not effect the purchasing decisions (Y), whereas information quality (X3) have a positive and significant influence on the purchasing decisions (Y). It was proof that if the quality of information on social media marketing is getting better, then the purchasing decisions of Soba Padu will increase by the interested of consumer to buy. It can made the increase of sales performance so the Soba Padu SMEs will be able to maintain business continuity.